KEY FACTORS IN WORKING CAPITAL MANAGEMENT IN THE BRAZILIAN MARKET - Wilson Toshiro Nakamura; Nathalie Vicente Nakamura Palombin (RAE: Revista de Administração de Empresas, 2012)
Many studies have been conducted in corporate finance regarding long-term investment and financing decisions. However, short-term asset investments play a significant role in the balance sheet of companies. Moreover, financial managers dedicate significantamounts of time and effort to the subject of working capital management, balancing current assets and liabilities. This paper provides insights regarding the key factors of working capital management by exploring the internal variables of a number of companies. This study used data from 2,976 Brazilian public companies from 2001 to 2008, and found that debt level, size and growth rate can affect the working capital management of companies.